Composite clarifying agent for preparing high-silica fiber yarn and preparation method of composite clarifying agent
By using a composite clarifier composed of soda ash and sodium pyromonate, the problem of decomposing and producing harmful gases at high temperatures in the prior art is solved, and environmentally friendly and safe preparation of high-temperature glass fiber yarns is achieved, with good economic and social benefits.
Patent Information
- Application Number
- CN202411894834.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-18
AI Technical Summary
The clarifiers used in the prior art will decompose at high temperatures to produce heavy metals and toxic gases that are harmful to the environment, resulting in environmental pollution and health risks.
A composite clarifier consisting of 20 to 25 parts by mass of soda ash and 75 to 80 parts by mass of sodium pyromonate is prepared by a solid phase low temperature synthesis method to avoid the generation of harmful gases at high temperatures.
It realizes that the clarifier does not produce nitrogen oxides, sulfur oxides, cerium oxides and arsenic oxide gases at high temperatures, reduces the harm to the environment and operators, improves the whiteness, fracture strength and SiO2 content of glass fiber yarns, and reduces waste liquid and waste gas emissions.
Smart Images

Figure CN119841545A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite clarifier and a preparation method thereof, in particular to a composite clarifier and a preparation method thereof and a method for producing ternary high-silica glass fiber yarn using the clarifier. Background Art
[0002] High silica glass fiber was first industrially produced by HIThompson in the United States based on the research of Owens Corning Glass Fiber Company. Its manufacturing method is to select appropriate original glass components, make various products such as cloth and yarn according to the ordinary glass fiber production process, and then leach out the acid-soluble components in the glass through acid leaching to make the SiO2 enrichment content reach more than 96%. After thermal sintering and shaping, high silica glass fiber with temperature resistance close to quartz fiber is obtained. The original glass components of high silica fiber produced in my country are mainly SiO2-B2O3-Na2O ternary system. At the same time, in order to reduce costs and meet the needs of high performance and special uses, E glass and SiO2-Na2O binary system glass are also used as original components to develop and produce high silica glass fiber and products.
[0003] CN200710110641.2 provides a glass-ceramic and a method for manufacturing glass-ceramic, wherein the glass-ceramic can maintain the characteristic physical properties of the glass-ceramic of the Li2O-Al2O3 system or the Li2O-Al2O3-SiO2 system, and reduce the content of arsenic and antimony components as much as possible, or contain no arsenic and antimony components. However, CeO2 is used as a clarifier in the glass-ceramic, and CeO2 will decompose heavy metal cerium at high temperature, thereby polluting the environment. CN201110161096.6 relates to a method for preparing transparent glass or transparent drawn glass by applying a specific clarification method, wherein the following sulfate clarifier is used as a clarifier in a limited amount, and the sulfate clarifier is selected from alkali metal sulfate, alkaline earth metal sulfate or a mixture thereof. However, sulfate clarifiers are high-temperature clarifiers, and their decomposition product SO2 pollutes the atmosphere.
[0004] CN201210003114.2 discloses a solar glass for oxyfuel furnace, which includes 70-75% SiO2, 0.1-2.5% Al2O3, 13.5-15% Na2O, 8-11% CaO, 0.5-4% MgO, 0.01-0.4% CeO2, 0.2-1% F, and 0.006-0.009% Fe2O by weight. The glass clarifier in the invention uses sodium fluorosilicate, which replaces the traditional sodium pyroantimonate. Although the cost of glass raw materials is reduced, during the melting of fluoride, part of the fluorine will generate hydrogen fluoride, silicon fluoride, and sodium fluoride, which are more toxic than sulfur dioxide. When using, the impact on the atmosphere should be considered.
[0005] CN201280006522.1 discloses a high-strength alkali metal-aluminosilicate glass characterized by excellent solubility, finability and processability. The formula contains 0-1.5 wt.% of a fining agent, such as As2O3, Sb2O3, CeO2, SnO2, Cl - 、F - 、(SO4) 2- and their combinations. It also allows the production of glass containing a small amount of one or both of antimony oxide and arsenic oxide. As2O3 used in the past is a good clarifier, but it is a toxic substance. The pollution to the environment during transportation, storage and use, and the strict requirements on the hygiene and safety of glass products in use, have increasingly restricted its use. Among them, Cl - 、F - 、(SO 4) 2- It will also produce toxic gases that pollute the environment.
[0006] CN201310001813.8 discloses a composite clarifier and a preparation method thereof, characterized in that it is compounded from 10 parts of cerium oxide, 20 parts of antimony oxide, 3 parts of lepidolite and 60 parts of calcium sulfate. The composite clarifier is compounded from cerium oxide, antimony oxide, lepidolite and calcium sulfate, overcoming the problem of high cost of using single cerium oxide, antimony oxide and lepidolite as clarifiers. Although diamine has low toxicity, the SO2 generated by the volatilization of sulfide has great harm to the environment.
[0007] CN201310308871.5 discloses a clarifier for TFT-LCD substrate glass and a preparation method thereof, which comprises, by mass percentage, 0.5-5% of variable valence oxide, 92-99.5% of oxygen donor and 0-5% of chloride salt. The invention uses variable valence oxide, oxygen donor and chloride salt to prepare a clarifier for TFT-LCD substrate glass. The inorganic salt oxygen donor is one or two of nitrate and sulfate. However, nitrate, sulfate and chloride salt will volatilize to produce gases that are harmful to the environment.
[0008] N201380010589.7 relates to a method for manufacturing bubble-free glass, wherein at least one alkali metal sulfate or at least one alkaline earth metal sulfate is added to the glass batch as one or more fining agents. The fining agent mentioned in this patent also contains sulfides that volatilize harmful gases.
[0009] CN201410371711.X discloses a method for preparing a high-transparency borosilicate glass tube. Sodium chloride and cerium oxide are selected as clarifiers used in the preparation of the high-borosilicate glass tube, which volatilize to produce harmful gases and heavy metals, causing environmental pollution.
[0010] CN201910065542.X discloses a composite clarifier for float process production of ultra-white glass, which contains the following components: sulfate, cerium oxide, nitrate and sodium antimonate. The clarifier mentioned in this patent also contains sulfides and nitrogen oxides that are harmful to the environment.
[0011] CN202110026062.X discloses a clarifier for medium borosilicate glass. The clarifier contains NaCl, CaF2, NaSiF6 and optionally CeO2; the glass clarifier uses specific components to prepare medium borosilicate glass with few bubbles and excellent properties, effectively improving the clarification effect, but contains fluoride and cerium oxide that are volatilized and harmful to the environment.
[0012] CN201811388840.4 provides a new composite clarifier for photovoltaic glass, including the following components by mass fraction: 10% to 15% antimony trioxide, 37% to 40% nitrate, and 45% to 50% cerium oxide. The use of the composite clarifier in the invention has better clarification and decolorization effects than a single clarifier and decolorizer, has low toxicity, low cost, and the emission of nitrogen oxides will be reduced accordingly, but a small amount of nitrogen oxides will also cause pollution to the environment.
[0013] CN202010359879.4 discloses a composite clarifier, borosilicate glass and a preparation method thereof, wherein the composite clarifier is used for borosilicate glass, and the composite clarifier includes 30-70wt% of ammonium chloride and 20-70wt% of sulfate, and in addition, A=sulfate / ammonium chloride, and A is 0.43-2.33. The composite clarifier of the invention does not contain arsenic and antimony, and the borosilicate glass produced by using the composite clarifier has a good clarification effect, but it will volatilize chlorine or sulfide gas, which is harmful to the environment.
[0014] All the above inventions contain nitrogen oxides, sulfides, fluorides, chlorides, or volatile substances harmful to the environment, such as harmful arsenic. Therefore, it is necessary to develop a composite clarifier that is environmentally friendly, pollution-free, and less harmful to operators. Summary of the invention
[0015] In order to overcome the problem of the above-mentioned prior art containing nitrogen oxides, sulfides, fluorides and chlorides, or containing harmful arsenic and other volatile substances harmful to the environment, the present invention proposes a composite clarifier for preparing high-silica fiber yarn and a preparation method thereof.
[0016] The composite clarifier provided by the invention consists of 20-25 parts by mass of soda ash and 75-80 parts by mass of sodium pyroantimonate.
[0017] The specific process of preparing high-silica fiber yarn proposed by the present invention is as follows:
[0018] Step 1, preparation of composite clarifier:
[0019] Weigh the soda ash and sodium pyroantimonate in proportion.
[0020] Mix the weighed soda ash and sodium pyroantimonate evenly and pour them into a corundum crucible. Put the crucible into a muffle furnace for heat preservation and firing; after the heat preservation is completed, cool it down to room temperature. Take out the material in the crucible, crush it, and filter it with a 100-mesh standard sieve to obtain a granular composite clarifier.
[0021] The heating rate of the muffle furnace is 10°C / min; the firing temperature is 500-550°C, and the heat preservation firing time is 60-120min.
[0022] The cooling rate of the muffle furnace is 3-5°C / min.
[0023] Step 2, preparation of batch materials:
[0024] In parts by mass, weigh 62 to 66 parts by mass of quartz sand, 3 to 5 parts by mass of albite, 13 to 17.5 parts by mass of borax, 13 to 15 parts by mass of boric acid, 3 to 6 parts by mass of soda ash and 0.1 to 0.5 parts by mass of a composite clarifier; add the weighed materials into a batching tank and mix them thoroughly to obtain a powdery batch material.
[0025] Step 3, preparation of high silica glass fiber precursor:
[0026] The platinum wire drawing furnace is heated to 1390-1415° C. The obtained batch materials are added to the platinum wire drawing furnace in batches for melting to obtain uniform glass liquid; the interval between two adjacent additions is 15 minutes.
[0027] The glass liquid flows out through the liquid outlet hole at the bottom of the platinum wire drawing furnace, is naturally air-cooled, and then is pulled by a wire drawing machine and wound on a wire drawing machine head to form high-silica glass fiber raw yarn.
[0028] The diameter of the liquid outlet hole is 1.6 mm. The rotation speed of the wire drawing machine is 3100-3500 r / min. The diameter of the obtained high-silica glass fiber raw yarn is 7 μm, and the linear density is 15-17 Tex.
[0029] Step 4, preparation of ternary high silica glass fiber yarn:
[0030] The high-silica glass fiber raw yarn obtained in step 3 is synthesized into six bundles, and then pickled with hydrochloric acid, dried and calcined to obtain a ternary high-silica glass fiber yarn with a silica content of >96%.
[0031] The hydrochloric acid pickling temperature is 90°C, the drying temperature is 105°C, and the calcination temperature is 650°C.
[0032] The present invention is a composite clarifier that does not generate nitrogen oxides, sulfur oxides, cerium oxide and arsenic oxide gases at high temperatures, and a method for producing ternary high-silica glass fiber yarn using the composite clarifier. After the prepared composite clarifier is degassed at high temperature, the residual material will not have a harmful effect on the ternary high-silica glass fiber yarn. The ternary high-silica glass prepared by using the composite clarifier has low bubble content, high glass melting efficiency and high whiteness. The prepared yarn has high breaking strength, high SiO2 content, and low heat loss and shrinkage. The preparation process of the present invention has no waste liquid and waste gas emissions, has little harm to operators and the environment, and has good economic and social benefits.
[0033] Compared with the prior art, the present invention has the following beneficial technical effects:
[0034] The present invention prepares a high-temperature composite clarifier used for ternary high-silica glass fiber yarn by adopting a solid-phase low-temperature synthesis method, and the raw materials do not contain nitrogen oxides, sulfur oxides, cerium oxide, arsenic oxide, etc., which will release toxic gases harmful to the environment at high temperatures. After the prepared composite clarifier is degassed at high temperature, the residual material will not have a harmful effect on the ternary high-silica glass fiber yarn. The ternary high-silica glass fiber yarn prepared by the composite clarifier has high whiteness, high breaking strength, high SiO2 content, and low heat loss and shrinkage. The preparation process of the present invention has no waste liquid and waste gas emissions, is less harmful to operators and the environment, and has good economic and social benefits. The ternary high-silica glass fiber yarn prepared by the present invention has a softening point close to 1700°C, can be used for a long time in an environment of 900°C, can instantly withstand thousands of degrees of airflow scouring, and can be widely used in spacecraft thermal ablation protection materials, high-temperature insulation and fireproof materials, high-temperature insulation materials, high-temperature gas dust collection, liquid filtration, metal melting filtration purification and other purposes. The prepared ternary high-silica glass fiber yarn can also be used as a high-temperature-resistant, insulation-structural integrated multifunctional material. The prepared ternary high-silica glass fiber yarn can also be used to reinforce phenolic resin to make high-temperature-resistant and ablation-resistant composite materials of various structural forms, which are widely used in thermal protection of rockets, missiles and other aircraft.
[0035] At the same time, the composite clarifier can not only discharge and clarify the bubbles in the high-temperature molten glass, but also its decomposition products will not affect the molten glass and can be completely melted together with the molten glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1This is the XRD diffraction pattern of the composite clarifier crystal prepared in Example 1, where the abscissa is the diffraction angle and the ordinate is the diffraction peak intensity. From the test results, it can be seen that the main crystal phase formed is Na2Sb4O7.
[0037] Figure 2 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0038] The present invention relates to a composite clarifier for preparing high-silica fiber yarn and a preparation method thereof, and the technical scheme thereof will be described in detail through 6 embodiments.
[0039] The composite clarifier provided by the invention is composed of 20-25 parts by mass of soda ash and 75-80 parts by mass of sodium pyroantimonate, wherein both the soda ash and the sodium pyroantimonate are solid powders with a content of more than 98%.
[0040] The specific process of using the composite clarifier to prepare high-silica fiber yarn proposed by the present invention is as follows:
[0041] Step 1, composite clarifier components and preparation:
[0042] Weigh the soda ash and sodium pyroantimonate in proportion.
[0043] Mix the weighed soda ash and sodium antimonate evenly and pour them into a corundum crucible. Put the crucible into a muffle furnace and heat it to 500-550°C at a rate of 10°C / min and keep it warm for 60-120 minutes.
[0044] After the insulation is completed, the temperature is lowered to room temperature at a rate of 3-5°C / min. The material in the crucible is taken out, crushed and filtered with a 100-mesh standard sieve to obtain a granular composite clarifier.
[0045] Component contents and process parameters of each embodiment in step 1
[0046]
[0047]
[0048] Step 2: Preparation of batch materials:
[0049] In parts by mass, weigh 62 to 66 parts by mass of quartz sand, 3 to 5 parts by mass of albite, 13 to 17.5 parts by mass of borax, 13 to 15 parts by mass of boric acid, 3 to 6 parts by mass of soda ash and 0.1 to 0.5 parts by mass of a composite clarifier; add the weighed materials into a batching tank and mix them thoroughly to obtain a powdery batch material.
[0050] Step 3, preparation of high silica glass fiber precursor:
[0051] The platinum wire drawing furnace is heated to 1390-1415° C. The obtained batch materials are added to the platinum wire drawing furnace in batches for melting to obtain uniform glass liquid; the interval between two adjacent additions is 15 minutes.
[0052] The glass liquid flows out through the liquid outlet hole at the bottom of the platinum wire drawing furnace, is naturally air-cooled, and then is pulled by a wire drawing machine and wound on a wire drawing machine head to form high-silica glass fiber raw yarn.
[0053] The diameter of the liquid outlet hole is 1.6 mm. The rotation speed of the wire drawing machine is 3100-3500 r / min. The diameter of the obtained high-silica glass fiber raw yarn is 7 μm, and the linear density is 15-17 Tex.
[0054] Component contents and drawing equipment parameters of each embodiment in step 2
[0055]
[0056] Step 4: Preparation of ternary high silica glass fiber yarn
[0057] By using the existing technology, the high-silica glass fiber raw yarn obtained in step 3 is synthesized into six bundles, pickled with hydrochloric acid at 90°C, dried at 105°C and calcined at 650°C to obtain a ternary high-silica glass fiber yarn with a silica content of >96%.
[0058] Test results of high silica glass fiber yarn obtained by the present invention
[0059]
[0060] The present invention prepares a high-temperature composite clarifier used for ternary high-silica glass fiber yarn by adopting a solid-phase low-temperature synthesis method, and the raw materials do not contain nitrogen oxides, sulfur oxides, cerium oxide, arsenic oxide, etc., which will release toxic gases harmful to the environment at high temperatures. After the prepared composite clarifier is degassed at high temperature, the residual material will not cause harm to the environment. The ternary high-silica glass fiber yarn prepared by the composite clarifier has high whiteness, high breaking strength, high SiO2 content, and low heat loss and shrinkage. The preparation process of the present invention has no waste liquid and waste gas emissions, is less harmful to operators and the environment, and has good economic and social benefits. The ternary high-silica glass fiber yarn prepared by the present invention has a softening point close to 1700°C, can be used in a 900°C environment for a long time, can instantly withstand thousands of degrees of airflow scouring, and can be widely used in spacecraft thermal ablation protection materials, high-temperature insulation and fireproof materials, high-temperature insulation materials, high-temperature gas dust collection, liquid filtration, metal melting filtration purification and other purposes. The prepared ternary high-silica glass fiber yarn can also be used as a high-temperature-resistant, insulation-structural integrated multifunctional material. The prepared ternary high-silica glass fiber yarn can also be used to reinforce phenolic resin to make high-temperature-resistant and ablation-resistant composite materials of various structural forms, which are widely used in thermal protection of rockets, missiles and other aerospace vehicles.
Claims
1. A composite clarifier for preparing high-silica fiber yarn, characterized in that: The invention is composed of 20 to 25 parts by weight of soda ash and 75 to 80 parts by weight of sodium pyroantimonate.
2. A method for preparing high-silica fiber yarn using the composite clarifier according to claim 1, characterized in that: The specific process is as follows: Step 1, preparation of composite clarifier: Weigh the soda ash and sodium pyroantimonate in proportion; The weighed soda ash and sodium antimonate are mixed evenly and poured into a corundum crucible; the crucible is placed in a muffle furnace for heat preservation and firing; after the heat preservation is completed, the crucible is cooled to room temperature; the material in the crucible is taken out, crushed and filtered with a 100-mesh standard sieve to obtain a granular composite clarifier; Step 2, preparation of batch materials: In parts by mass, weigh 62 to 66 parts by mass of quartz sand, 3 to 5 parts by mass of albite, 13 to 17.5 parts by mass of borax, 13 to 15 parts by mass of boric acid, 3 to 6 parts by mass of soda ash and 0.1 to 0.5 parts by mass of a composite clarifier; add the weighed materials into a batching tank and mix them thoroughly to obtain a powdered batch material; Step 3, preparation of high silica glass fiber precursor: The platinum wire drawing furnace is heated to 1390-1415° C.; the obtained batch materials are added to the platinum wire drawing furnace in batches for melting to obtain uniform glass liquid; the interval between two adjacent additions is 15 minutes; The glass liquid flows out through the liquid outlet hole at the bottom of the platinum drawing furnace, is naturally cooled by air, and then is pulled by a drawing machine and wound on a drawing machine head to form high-silica glass fiber raw yarn; Step 4, preparation of ternary high silica glass fiber yarn: The high-silica glass fiber raw yarn obtained in step 3 is synthesized into six bundles, and then pickled with hydrochloric acid, dried and calcined to obtain a ternary high-silica glass fiber yarn with a silica content of >96%.
3. The method for preparing high-silica fiber yarn using a composite clarifier as claimed in claim 1, characterized in that: In step 1, the heating rate of the muffle furnace is 10°C / min; the firing temperature is 500-550°C, and the heat preservation firing time is 60-120min.
4. The method for preparing high-silica fiber yarn using a composite clarifier as claimed in claim 1, characterized in that: In step 1, the cooling rate of the muffle furnace is 3-5°C / min.
5. The method for preparing high-silica fiber yarn using a composite clarifier as claimed in claim 1, characterized in that: The aperture of the liquid outlet is 1.6 mm; the rotation speed of the wire drawing machine is 3100-3500 r / min; the diameter of the obtained high-silica glass fiber raw yarn is 7 μm, and the linear density is 15-17 Tex.
6. The method for preparing high-silica fiber yarn using a composite clarifier as claimed in claim 1, characterized in that: In step 4, the hydrochloric acid pickling temperature is 90°C, the drying temperature is 105°C, and the calcination temperature is 650°C.
Citation Information
Patent Citations
Crystallized glass and method for producing crystallized glass
CN101085699A
Method for producing clear glass or clear drawn glass by utilizing special refining process
CN102363553A
Solar glass for full-oxygen combustion tank furnace
CN102557433A
Compound clarifying agent, preparation method thereof and method for preparing E glass fiber by adopting compound clarifying agent
CN103058513A
Clarifying agent used for TFT-LCD substrate glass and preparation method thereof
CN103408223A